Acute exercise effects on the immune system - Rowbottom, D. G.; Green, K. J. (Medicine & Science in Sports & Exercise, 2000)
Purpose: In recent years, health professionals have placed increased attention on the benefits of physical activity for maintaining health in the general population as well as regaining health in many disease states. Conversely, reports of apparent decreases in immune cell function after acute exercise are widespread in the literature. The purpose of this article is to evaluate critically the available data and currently employed methods, with the aim of establishing whether genuine or artefactual alterations of immune function are being reported. During and immediately after exercise, the total number of white blood cells in peripheral blood samples increases, such that the relative proportions of cell types within the leukocyte pool are altered. A number of important areas of discussion arise from these shifts in the number of circulating cells after exercise, not least of which is the artefactual effects they may have on currently employed assays of immune cell function. Recent advances in methodology are beginning to call into question the assumption that acute exercise has any genuine immunosuppressive effect. Conclusion: At present, there is little evidence to suggest that the range of acute exercise intensities and durations recommended by ACSM has a major detrimental effect on the function of individual T- and B-lymphocytes, natural killer cells and neutrophils Although individual cells may not be as adversely affected as previously supposed, it is unclear whether the numerical content of the circulating population is an important clinical consideration.